Constituição e sociedade: uma análise sobre a (re)formulação da arquitetura do Estado-Nação na Assembleia Nacional Constituinte de 1933 - Cabral, Rafael Lamera (2010)
The objective of this research was to examine, within the platform for social change that is promoted by the Revolution of 1930 until reconstitucionalização the country with the National Constituent Assembly - NCA in 1933, the themes (i) federalism, (ii) regulation work and (iii) class representation were incorporated, through the political disputes, when it was projected to be (re) formulation in the architecture of the Brazilian Nation-State. The constitutional process performed showed the presence of the state politics (through the issues and social work) and Law (in its formatting in the legal framework Law of State) would be critical to the passage of modernity in Brazil. This constitution would be the first of the historic constitutional political and legal thinking about the modern Brazilian and both had important characteristics, because it gave voice to political and social actors in the ANC (the recruitment election result was a generalization multiplied in their representations to the model classical liberal model and the class/organic, with the participation of women, capital and labor). More than institutional innovations in engineering these changes expressed the structural transformation of Brazilian society in the period. If the new actors and interests could not be concerted in the frame of the old Constitution, it became necessary to further the political agenda and a new form of negotiation. Analyses were performed by mapping three phases of political disputes culminating in the final text of the Constitution: it was to a) draft constitution sponsored by the subcommittee of the Foreign Office (official proposal of the Provisional Government), b) discussions constituents (represented by opinion of the 26) and c) the final text of the Constitution. Across these three crops appear in the disputes highlighted the themes of federalism, the regulation of labor rights and class representation, expressions of changes in the modernization process underway in the country as resources and strategies with regard to constitutional procedure.